Phytochemical Analysis, Antioxidant Potential and Antibacterial Activities of Different Anatomical Parts of Hypericum cordifolium Choisy - Sujana Sapkota; Alishma Maharjan; Sanjeeta Tiwari; Meena Rajbhandari (The Scientific World Journal)
The genus Hypericum comprises a large number of species. The flower, leaf, stem, and root of the Hypericum species are widely used in traditional medicine in different cultures. Many Hypericum species have been well investigated phytochemically and pharmacologically. However, only a few reports are available on the H. cordifolium native to Nepal. The present study aims to evaluate the phytochemical composition of different extracts, qualitative analysis of methanol extract of the flower and leaf using thin-layer chromatography (TLC), and the antioxidant properties of components by the TLC-DPPH. assay. The phenolic and flavonoid contents were estimated in different extracts of the leaf and stem, and their antioxidant and antibacterial activities were evaluated. In the phytochemical screening, phenolics and flavonoids were present in ethyl acetate, methanol, and 50% aq methanol extracts of both the leaf and stem. In TLC analysis, the methanol extract of flowers showed the presence of 11 compounds and the leaf extract showed the presence of 8 compounds. Both extracts contained chlorogenic acid and mangiferin. Hyperoside and quercetin were present only in the flower extract. In the TLC-DPPH. assay, almost all of the flower extracts and 5 compounds of the leaf extract showed radical scavenging potential. Estimation of phenolics and flavonoids showed that all the leaf extracts showed higher amounts of phenolics and flavonoids than stem extracts. Among leaf extracts, greater amounts of phenolics were detected in 50% aqueous methanol extract (261.25 ± 1.66 GAE/g extract) and greater amounts of flavonoids were detected in methanol extract (232.60 ± 10.52 CE/g extract). Among stem extracts, greater amounts of flavonoids were detected in the methanol extract (155.12 ± 4.30 CE/g extract). In the DPPH radical scavenging assay, the methanol extract of the leaf showed IC50 60.85 ± 2.67 µg/ml and 50% aq. methanol extract of the leaf showed IC50 63.09 ± 2.98 µg/ml. The methanol extract of the stem showed IC50 89.39 ± 3.23 µg/ml, whereas ethyl acetate and 50% aq. methanol extract showed IC50 > 100 µg/ml. In the antibacterial assay, the methanol extract of the leaf showed the inhibition zone of 12-13 mm and the stem extract showed the inhibition zone of 7–11 mm against S. aureus, E. coli, and S. sonnei, whereas both extracts were inactive against S. typhi. The findings of this study support the traditional use of this plant in Nepal for the treatment of diseases associated with bacterial infections. The present study revealed that the underutilized anatomical parts of H. cordifolium could be the source of various bioactive phytochemicals like other Hypericum species.